Perinatal Risk Factors for Diabetes in Later Life - Kaijser, Magnus; Edstedt Bonamy, Anna-Karin; Akre, Olof; Cnattingius, Sven; Granath, Fredrik; Norman, Mikael; Ekbom, Anders (Diabetes (New York, N.Y.), 2009)
Perinatal Risk Factors for Diabetes in Later Life Magnus Kaijser 1 2 , Anna-Karin Edstedt Bonamy 3 , Olof Akre 1 , Sven Cnattingius 4 , Fredrik Granath 1 , Mikael Norman 5 and Anders Ekbom 1 1 Clinical Epidemiology Unit, Department of Medicine, Karolinska Institutet, Stockholm, Sweden 2 Department of Clinical Sciences, Danderyds Hospital, Stockholm, Sweden 3 Department of Woman and Child Health, Karolinska Institutet, Stockholm, Sweden 4 Department of Medical Epidemiology and Biostatistics, Karolinska Institutet, Stockholm, Sweden 5 Department of Clinical Science, Intervention and Technology, Karolinska Institutet, Stockholm, Sweden Corresponding author: Magnus Kaijser, magnus.kaijseratki.se Abstract OBJECTIVE— Low birth weight is consistently associated with an increased risk of type 2 diabetes in adulthood, but the individual contributions from poor fetal growth and preterm birth are not known. We therefore investigated the significance of these two factors separately. RESEARCH DESIGN AND METHODS— We identified a cohort of subjects born preterm or with low birth weight at term at four major delivery units in Sweden from 1925 through 1949. A comparison cohort of subjects was identified from the same source population. Of 6,425 subjects in all, 2,931 were born at <37 weeks of gestation and 2,176 had a birth weight <2,500 g. Disease occurrence among participants was assessed through nationwide hospital registers from 1987 through 2006. RESULTS— During follow-up, there were 508 cases of diabetes. Low birth weight was strongly negatively associated with risk of diabetes ( P for trend <0.0001). Both short gestational duration and poor fetal growth were associated with later diabetes ( P for trend <0.0001 and <0.0004, respectively). Very preterm birth (≤32 weeks of gestation at birth) was associated with a hazard ratio (HR) of 1.67 (95% CI 1.33–2.11) compared with term birth. Birth weights below 2 SDs of mean birth weight for gestational age were associated with an HR of 1.76 (1.30–2.38) compared with birth weights between the mean weight and the weight at 1 SD above the mean. CONCLUSIONS— Our results suggest that the association between low birth weight and diabetes is due to factors associated with both poor fetal growth and short gestational age. Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 9 December 2008. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted November 21, 2008. Received April 24, 2008. DIABETES